THE INFLUENCE OF RESEARCH ACTIVITIES ON THE FORMATION OF MOTIVATION FOR STUDYING PHYSICS - Pepke V.S.; Tastanov M.G.; Mongotov K.B. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
This article examines the influence of research activities on the development of motivation for studying physics in schoolchildren. In the context of modern education, special attention is paid to active learning methods that promote cognitive independence and interest in the subject. Research activities are viewed as a means of increasing students' intrinsic motivation, their engagement in the educational process, and their understanding of the practical significance of physics. Based on an analysis of the works of foreign and domestic scientists, a theoretical justification for the relationship between an activity-based approach and the development of sustainable academic interest is revealed. The article demonstrates that student participation in research projects, setting up experiments, and finding solutions to physics problems fosters cognitive activity, responsibility for the results, and self-confidence. A conclusion is drawn regarding the need to integrate the research method into the school physics education system as an effective way to develop cognitive motivation and scientific thinking.
Keywords: research activities; learning motivation; NATURAL SCIENCES::Physics::Elementary particle physics::Ion physics; activity-based approach; cognitive interest; school education; active learning methods